Adaptive comanagement to achieve climate‐ready fisheries. Issue 6 (30th March 2018) - Wilson, Jono R.; Lomonico, Serena; Bradley, Darcy; Sievanen, Leila; Dempsey, Tom; Bell, Michael; McAfee, Skyli; Costello, Christopher; Szuwalski, Cody; McGonigal, Huff; Fitzgerald, Sean; Gleason, Mary
Abstract: Climate‐related impacts to marine ecosystems threaten the biological, social, and economic resilience of the U.S. fishing industry. Changes in ocean conditions and variability in fisheries productivity have stimulated an effort to integrate climate information into fisheries science and management processes to inform more responsive decision‐making. However, institutional, capacity, and budget constraints within U.S. federal and state fisheries management agencies may hinder the potential to deliver climate‐ready strategies for many fisheries. We examine whether adaptive comanagement as a governance approach can enhance capacity and advance climate‐ready fisheries objectives. Adaptive comanagement may improve the quality of science and decision‐making needed to prepare for and respond to impacts of climate change in fisheries by taking advantage of skills, technology, and funding often not optimally utilized under the current governance system. We focus on the potential to improve information flows as a means to achieve climate‐ready fisheries via adaptive comanagement, but suggest that a greater level of partnership in the management process may be possible in the future after a period of formal experimentation and learning.